Monitoring of T790M in plasma ctDNA of advanced EGFR-mutant NSCLC patients on first- or second-generation tyrosine kinase inhibitors - Huang, Chun-Ta; Lin, Chih-An; Su, Te-Jen; Yang, Ching-Yao; Tsai, Tzu-Hsiu; Hsu, Chia-Lin; Liao, Wei-Yu; Chen, Kuan-Yu; Ho, Chao-Chi; Yu, Chong-Jen (BMC cancer, 2023)
The T790M mutation is the major resistance mechanism to first- and second-generation TKIs in EGFR-mutant NSCLC. This study aimed to investigate the utility of droplet digital PCR (ddPCR) for detection of T790M in plasma circulating tumor DNA (ctDNA), and explore its impact on prognosis. This prospective study enrolled 80 advanced lung adenocarcinoma patients treated with gefitinib, erlotinib, or afatinib for TKI-sensitizing mutations between 2015 and 2019. Plasma samples were collected before TKI therapy and at tri-monthly intervals thereafter. Genotyping of ctDNA for T790M was performed using a ddPCR EGFR Mutation Assay. Patients were followed up until the date of death or to the end of 2021. Seventy-five of 80 patients experienced progressive disease. Fifty-three (71%) of 75 patients underwent rebiopsy, and T790M mutation was identified in 53% (28/53) of samples. Meanwhile, plasma ddPCR detected T790M mutation in 23 (43%) of 53 patients. The concordance rate of T790M between ddPCR and rebiopsy was 76%, and ddPCR identified 4 additional T790M-positive patients. Ten (45%) of 22 patients who did not receive rebiopsy tested positive for T790M by ddPCR. Serial ddPCR analysis showed the time interval from detection of plasma T790M to objective progression was 1.1 (0-4.1) months. Compared to 28 patients with rebiopsy showing T790M, the overall survival of 14 patients with T790M detected solely by ddPCR was shorter(41.3 [95% CI, 36.6-46.0] vs. 26.6 months [95% CI, 9.9-43.3], respectively). Plasma ddPCR-based genotyping is a useful technology for detection and monitoring of the key actionable genomic alteration, namely, T790M, in patients treated with gefitinib, erlotinib, or afatinib for activating mutations, to achieve better patient care and outcome.